2017
DOI: 10.1108/nfs-03-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary feta cheese and butter on serum lipid profile and fatty acid composition in rat

Abstract: Purpose Cardiovascular diseases (CVDs) are the most common causes of death worldwide. Diets rich in saturated and trans-fatty acids are nutritional risk factors that foster the development of CVDs. The aim of this experimental study was to investigate the effects of dietary feta cheese and butter on serum lipid profile and fatty acid composition. Design/methodology/approach In all, 24 Wistar rats (eight weeks old) were fed with balanced high fat diets (24 per cent fat) including canola (control group) and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The control diet was based on the recommendations to the American Institute of Nutrition -(AIN-93) (Reeves et al, 1993) to which corn meal had been added, with or without cactus flour (Opuntia ficus indica), made with the stem of the plant. The western-style diet consisted of an adaptation of AIN-93M adjusted for total protein amount and including such ingredients as simple sugar, chocolate cookies, corn starch and fats from animal source (butter, cream milk, lard) and from vegetable (soya and maize oil) (Khodadadi and Karami, 2017;Vahidinia, 2016). The ingredients were processed to a dry consistency, of the control diet were mixed with oil and bound together then water was added.…”
Section: Dietsmentioning
confidence: 99%
“…The control diet was based on the recommendations to the American Institute of Nutrition -(AIN-93) (Reeves et al, 1993) to which corn meal had been added, with or without cactus flour (Opuntia ficus indica), made with the stem of the plant. The western-style diet consisted of an adaptation of AIN-93M adjusted for total protein amount and including such ingredients as simple sugar, chocolate cookies, corn starch and fats from animal source (butter, cream milk, lard) and from vegetable (soya and maize oil) (Khodadadi and Karami, 2017;Vahidinia, 2016). The ingredients were processed to a dry consistency, of the control diet were mixed with oil and bound together then water was added.…”
Section: Dietsmentioning
confidence: 99%
“…However, due to the impact of full‐fat dairy products on the increment of blood cholesterol and saturated fatty acids (SFAs), current US and Canadian dietary guidelines for cardiovascular health suggest the consumption of low‐fat dairy products (Hirahatake et al, 2020 ; Mozaffarian, 2019 ; Naghshi et al, 2022 ). The epidemiologic studies indicated the association of low‐fat dairy product intake with lower risk of metabolic syndrome incidences such as type 2 diabetes, blood pressure, and the improvement of lipid profile (Drouin‐Chartier et al, 2016 ; Khodadadi et al, 2017 ; Margolis et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%